Hubungan Tingkat Pengetahuan dan Minat Masyarakat Terhadap Pelayanan Gizi Berbasis Gen di Indonesia: Hubungan Tingkat Pengetahuan dan Minat Masyarakat dengan Pelayanan Gizi Berbasis Gen di Indonesia - Khouridhiya, Mumtaz; Aji, Arif Sabta; Herawati, Herni Dwi; Purnamasari, Sintha Dewi; Listiyana, Fani; Wulandari, Fatma Annisa; Surendran, Shelini (Amerta Nutrition, 2024)
Background: The rapid technological development has led to the emergence of gene-based nutrition services, which hold promise in reducing the prevalence of Non-Communicable Diseases (NCDs). However, a considerable portion of the population remains unaware of these innovative nutrition services. Objectives: This study aims to identify the correlation between the extent of public knowledge and their interest in gene-based nutrition services in Indonesia. Methods: This study used a cross-sectional design. This study was conducted online via the Qualtrics Survey platform during May-June 2023. The determination of the sample used a cluster sampling technique across five provinces in Indonesia. The research instrument used a questionnaire on socio-demographic characteristics and a validated structured questionnaire assessing knowledge and interest levels in gene-based nutrition services. Statistical data analysis employed the Chi-Square test. Results: This study involved a total of 439 respondents from five provinces in Indonesia. The majority of the respondents exhibited low levels of knowledge (51.7%) and interest (55.4%) in gene-based nutrition services. A statistically significant association was observed between knowledge and interest in gene-based nutrition services (p-value=0.029, PR=1.5, 95% CI=1.04-2.22). Conclusions: The findings of this study underline a relationship between the extent of knowledge and the level of interest in gene-based nutrition services in Indonesia. To increase public interest, it is necessary to increase knowledge regarding gene-based nutrition services through online media, nutritionists or print media that discuss nutrigenetics and nutrigenomics.